2009
DOI: 10.1073/pnas.0908563106
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of protein kinase C signaling protects prefrontal cortex dendritic spines and cognition from the effects of chronic stress

Abstract: The prefrontal cortex r regulates behavior, cognition, and emotion by using working memory. Prefrontal functions are impaired by stress exposure. Acute, stress-induced deficits arise from excessive protein kinase C (PKC) signaling, which diminishes prefrontal neuronal firing. Chronic stress additionally produces architectural changes, reducing dendritic complexity and spine density of cortico-cortical pyramidal neurons, thereby disrupting excitatory working memory networks. In vitro studies have found that sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
187
0
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(205 citation statements)
references
References 63 publications
12
187
0
6
Order By: Relevance
“…Importantly, the significant correlation of the degree of spine loss and the degree of cognitive impairment in individual mice supports a causal relationship, a conclusion strengthened by our finding that blocking stress-induced spine loss abrogated the memory impairments in the same mice. Together, and as proposed in the prefrontal cortex after chronic stress (84,85), these data suggest that stress causes loss of spines and thus reduction in the number of postsynaptic elements harboring glutamatergic receptors crucial for LTP, learning, and memory. These structural changes, in turn, underlie the poor cognitive function of the stressed mice.…”
Section: Discussionsupporting
confidence: 71%
“…Importantly, the significant correlation of the degree of spine loss and the degree of cognitive impairment in individual mice supports a causal relationship, a conclusion strengthened by our finding that blocking stress-induced spine loss abrogated the memory impairments in the same mice. Together, and as proposed in the prefrontal cortex after chronic stress (84,85), these data suggest that stress causes loss of spines and thus reduction in the number of postsynaptic elements harboring glutamatergic receptors crucial for LTP, learning, and memory. These structural changes, in turn, underlie the poor cognitive function of the stressed mice.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have shown that CRF facilitates the phosphorylation of PKC in PFC slices (Tan et al, 2004), whereas inhibiting PKC activity rescues chronic adult stress-induced apical dendritic spine loss in mPFC neurons and working memory deficits (Hains et al, 2009). Intriguingly, the protein levels of PKC isoforms increase rapidly around the first postnatal week (Roisin and Barbin, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…As shown by previous studies, postnatal stress exposure impairs the development of mPFC neurons and mPFC-dependent cognitive performance in adolescent and adult animals (Bock et al, 2005; Chocyk et al, 2013; Monroy et al, 2010). However, although glucocorticoids (Wellman, 2001), glutamatergic neurotransmission (Martin and Wellman, 2011), and protein kinase C (PKC) (Hains et al, 2009) have been proposed to mediate the adverse effects of chronic adult stress on the structure and function of mPFC, a comprehensive insight into the mechanisms underlying early-life stress-evoked prefrontal abnormalities is still lacking.…”
Section: Introductionmentioning
confidence: 94%
“…Overactivity of PKC leads to marked retraction of dendrites and loss of spine density in the prefrontal cortex and hippocampus and further disrupts working memory, spatial learning and memory performance (Hains et al, 2009;Wood et al, 2004;Birnbaum et al, 2004). In addition, genetic alteration leading to overactivated PKC signalling has been reported in bipolar disorder (Baum et al, 2008) and schizophrenia (Mirnics et al, 2001).…”
Section: Discussionmentioning
confidence: 99%